Pemodelan User Interface dan User Experience pada Website E-Commerce Bitcom Computer Menggunakan Metode User Centered Design - Tobi Fiambodo Syech Maulana; Hanifah Permatasari; Intan Oktaviani (IJAI (Indonesian Journal of Applied Informatics), 2024)
Abstrak Bitcom Computer adalah sebuah toko komputer yang menyediakan berbagai aksesoris dan peralatan IT, layanan servis komputer, serta pemasangan CCTV. Permasalahan yang terjadi di Bitcom Computer adalah proses pencatatan transaksi masih menggunakan nota tulis, sulitnya merekap laporan penjualan, dan kurang maksimalnya promosi layanan. Solusi awal yang dapat ditawarkan adalah membuat pemodelan UI/UX website e-commerce, dikarenakan UI/UX merupakan faktor penting agar pengguna dapat merasa nyaman saat menggunakan sebuah website/aplikasi. Penelitian skripsi ini bertujuan untuk menjelaskan pemodelan UI/UX website e-commerce Bitcom Computer menggunakan metode User Centered Design (UCD) yang memiliki 5 tahap, yaitu Plan the User-Centered Process, Specify the Context of Use, Specify the User and Organizational Requirements, Produce Design Solutions, dan Evaluate the Designs Against Requirements. Rancangan UI/UX dibuat dalam bentuk prototype menggunakan Figma. Jumlah partisipan dalam penelitian ini sebanyak 15 orang, terdiri dari 3 kategori yaitu pihak internal Bitcom Computer, pelanggan Bitcom Computer, dan masyarakat umum. Prototype berhasil diujikan kepada 15 partisipan tersebut dengan sekali perbaikan menggunakan platform Maze Design dan dibuat menjadi 3 jenis skenario pengujian yaitu pengujian untuk customer, manajer dan admin Bitcom Computer. Skor akhir usability diperoleh sebesar 97 untuk skenario customer, serta masing-masing skor usability sebesar 100 pada skenario manajer dan admin Bitcom Computer. Dengan demikian menunjukkan bahwa prototype desain website e-commerce Bitcom Computer mudah digunakan dan sesuai dengan kebutuhan pengguna.=================================================AbstractBitcom Computer is a computer shop that provides various accessories and IT equipment, computer service services, and CCTV installation. The problems that occur at Bitcom Computer are that the process of recording transactions still uses written notes, the difficulty of recapitulating sales reports, and the lack of maximum service promotion. The initial solution that can be offered is to model the UI/UX of an e-commerce website, because UI/UX is an important factor so that users can feel comfortable when using a website/application. This thesis research aims to explain the UI/UX modeling of the Bitcom Computer e-commerce website using the User Centered Design (UCD) method which has 5 stages, namely Plan the User-Centered Process, Specify the Context of Use, Specify the User and Organizational Requirements, Produce Design Solutions, and Evaluate the Designs Against Requirements. The UI/UX design is made in prototype form using Figma. The number of participants in this study were 15 people, consisting of 3 categories, namely Bitcom Computer internal parties, Bitcom Computer customers, and the general public. The prototype was successfully tested on 15 participants with one fix using the Maze Design platform and made into 3 types of test scenarios, namely testing for customers, managers and admins of Bitcom Computer. The final usability score was 97 for the customer scenario, and each usability score was 100 for the Bitcom Computer manager and admin scenario. This shows that the Bitcom Computer e-commerce website design prototype is easy to use and meets user needs.